Beyond Christian hip hop: a move toward Christians and hip hop - Gault, Erika; Harris, Travis (Routledge studies in hip hop and religion, 2020)
"Christians and Christianity have been central to Hip Hop since its inception. This book explores the intersection of Christians and Hip Hop and the multiple outcomes of this intersection. It lays out the ways in which Christians and Hip Hop overlap and diverge. The intersection of Christians and Hip Hop brings together African diasporic cultures, lives, memories and worldviews. Moving beyond the focus on rappers and so-called "Christian Hip Hop," each chapter explores three major themes of the book: identifying Hip Hop, irreconcilable Christianity, and boundaries.There is a self-identified Christian Hip Hop (CHH) community that has received some scholarly attention. At the same time, scholars have analyzed Christianity and Hip Hop without focusing on the self-identified community. This book brings these various conversations together and show, through these three themes, the complexities of the intersection of Christians and Hip Hop. Hip Hop is more than rap music, it is an African diasporic phenomenon. These three themes elucidate the many characteristics of the intersection between Christians and Hip Hop and our reasoning for going beyond "Christian Hip Hop." This collection is a multi-faceted view of how religious belief plays a role in Hip Hoppas' lives and community. It will, therefore, be of great interest to scholars of Religion and Hip Hop, Hip Hop, African Diasporas, Religion and the Arts, Religion and Race and Black Theology as well as Religious Studies more generally"--